Analysis of Old Town Development on Jalan Asahan, Tanjungbalai City - Iskandar Zulkarnaen; Abdi Sugiarto; Cut Nuraini (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This study aims to examine the Analysis of Old Town Development on Jalan Asahan, Tanjungbalai City.Qualitative research is an approach used to understand social phenomena through the views of the peopleinvolved in the phenomenon. Data Collection Techniques Data collection methods in qualitative research can becarried out through several techniques. This research will categorize data based on key themes, such as: Publicperception of development benefits. Weaknesses and challenges in the development of Kota Tua. Thecommunity's expectations for the future of the Region. The qualitative research method used in the analysis ofthe development of Kota Tua on Jalan Asahan is expected to provide a deep understanding of the perspective ofthe community and related stakeholders. The results of the research on the Old Town Area on Jalan Asahan havehigh historical value and historical architectural richness. The main challenges in the development of this areainclude limited funding, lack of maintenance of historical buildings, and low public awareness regarding theimportance of preserving cultural heritage. The role of the government and the community is very important insupporting the development of Kota Tua. The development of Kota Tua is expected to boost the local economyby attracting tourists and creating new jobs. Overall, the development of Kota Tua on Jalan Asahan requires aholistic approach involving economic, cultural, social, and environmental aspects to realize a sustainablehistorical area and provide benefits to the surrounding community